165 A NICE accredited guideline for the management of malignant ascites. (14th March 2023) - Shaw, Laura; Mclintock, Sara; Scott, Aileen; Fradsham, Sarah; Corrigan, Margaret; Tobin, Lynn; Stanley, Sarah; Evans, Katie; Gilman, Connie
Abstract : Introduction: Ascites is the accumulation of fluid in the peritoneal cavity, often associated with a poor quality of life and poor prognosis. There is limited national guidance on management of malignant ascites .This guideline has been produced to enable healthcare professionals to make evidence-based, patient-centred decisions about the management of ascites in patients with life-limiting cancer. Method: A comprehensive literature search was conducted, including a key word search in the Cochrane and NICE databases. Articles were graded using SIGN criteria. Surveys of professionals/clinical notes were performed to assess current practice. These were collated and reviewed by the guideline development group (CDG) and a guideline drafted. Results: Medical management: Evidence for diuretics less clear in malignant ascites. Serum-ascites albumin gradient (SAAG) can be calculated from ascitic tap. SAAG >1.1g/dL most likely to benefit. Spironolactone is first line diuretic, starting at 100mg and titrated to 400mg every 3–4 days as required. If insufficient response, furosemide can be added. Large volume paracentesis (LVP): Accepted standard of care for large volume tense ascites if diuretic resistance/intolerance. Limited evidence to support use of human albumin solution in LVP for malignant ascites. There are limited indications for a drain to be clamped. Drain removal after six hours is recommended. Permanent indwelling peritoneal catheters: May help with symptom control by avoiding repeated LVP. PleurX peritoneal catheter is recommended by NICE as an option to manage refractory malignant ascites. The CDG recommend considering after two LVP. Estimated cost saving of £1051 for PleurX insertion compared to in-patient LVP. Conclusion: Malignant ascites is a condition that has a significant impact on a patient's quality of life. We have collated a NICE accredited guideline to help consolidate evidence and standardise the approach to management of these patients.